Learning from the "best": The impact of tax-benefit systems in Africa - Olivier Bargain; H. Xavier Jara; Prudence Kwenda-Magejo; Miracle Ntuli (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Redistributive systems in Africa are still in their infancy but are constantly expanding in order to finance increasing public spending. This paper aims at characterizing the redistributive potential of six African countries: Ghana, Zambia, Mozambique, Tanzania, Ethiopia, and South Africa. These countries show contrasted situations in terms of income distribution. We assess the role of tax-benefit systems to explain these differences. Using newly developed tax-benefit microsimulations for all six countries, we produce counterfactual simulations whereby the system of the most (least) redistributive country is applied to the population of all other countries. In this way, we can decompose the total country difference in income distribution between the contribution of tax-benefit policies versus the contribution of other factors (market income distributions, demographics, etc.). This analysis contributes to the recent literature on the redistributive role of socio-fiscal policies in developing countries and highlights the role of microsimulation techniques to characterize how different African countries can learn from each other to improve social protection and reduce inequality.
Keywords: H23; H53; I32; 330; tax-benefit policy; microsimulation; inequality; poverty; Africa